Menstrually related symptom changes in women with treatment-responsive bipolar disorder - Karadag, F; Akdeniz, F; Erten, E; Pirildar, S; Yucel, B; Polat, A; Atmaca, M (Wiley, 2004)
Objective: In the present study, we aimed to evaluate menstrually related symptom changes in euthymic women with treatment-responsive bipolar disorder (BD) compared with healthy control subjects and investigate the presence of premenstrual dysphoric disorder (PMDD). Methods: Thirty-four euthymic women with treatment-responsive BD on mood-stabilizers (lithium and/or valproate) for at least 6 months and 35 control Subjects with no history of medical/mental disorder between ages of 18 and 35 years with regular menstrual cycles were prospectively followed up for at least two consecutive menstrual cycles using the Daily Record of Severity of Problems-Short Form (DRSP). Each subject was administered the retrospective self-report questionnaire, Premenstrual Assessment Form (PAF) in the first postmenstrual phase of the menstrual cycle. venous blood samples were collected between 19 and 22 days of menstrual cycle to evaluate ovulation by measuring the serum progesterone levels. Results: The differences in mean age, age of onset of menses, cycle length and bleeding length did not appear to be significantly meaningful between groups. In the retrospective assessment of premenstrual symptom changes, controls complained more than women with BD. More controls showed a 30% change in DRSP and in depressive and physical sub-groups than the women with BD. Controls demonstrated a significant increase compared with treatment-responsive BD patients in total, depressive, anxiety and attention sub-group scores of DRSP from the postmenstrual to the premenstrual phase, whereas the scores of vegetative symptoms of controls and women with BD did not differ significantly during one cycle or both. Significant menstrual cycle effect was observed in both groups. Conclusion: Within the limitations of the study, the results suggest that ongoing mood-stabilizing treatment may have a prophylactic effect against premenstrual symptom changes in women with treatment-responsive BD.
155th Annual Meeting of the American-Psychiatric-Association -- MAY 18-23, 2002 -- PHILADELPHIA, PA
Keywords: bipolar disorder; mood-stabilizer; premenstrual dysphoric disorder; premenstrual symptoms; women